2018
DOI: 10.3329/ijarit.v7i2.35320
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial efficacy of Trichoderma spp. and Pseudomonas fluorescens to enhance suppression of cell wall degrading enzymes produced by Fusarium wilt of Arachis hypogaea.L

Abstract: Fusarium oxysporum, the soil borne pathogen causes vascular wilt, on majority of crop plants. It has been demonstrated that two different species of Trichoderma and Pseudomonas fluorescens suppress disease by different mechanisms. Therefore, application of a mixture of these biocontrol agents, and thus of several suppressive mechanisms, may represent a viable control strategy. A necessity for biocontrol by combinations of biocontrol agents can be the compatibility of the co-inoculated micro-organisms. Hence, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…This study revealed that 11 interactions among Trichoderma and Pseudomonas strains were compatible with each other as no zone of inhibition was observed between the strains. Our findings were in agreement with [ 17 – 19 , 43 ], who reported that, the compatibility of Pseudomonas and Trichoderma species under in-vitro assays. In our study, the promising potential antagonistic Pseudomonas and Trichoderma strains displayed compatibility under in-vitro conditions.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that 11 interactions among Trichoderma and Pseudomonas strains were compatible with each other as no zone of inhibition was observed between the strains. Our findings were in agreement with [ 17 – 19 , 43 ], who reported that, the compatibility of Pseudomonas and Trichoderma species under in-vitro assays. In our study, the promising potential antagonistic Pseudomonas and Trichoderma strains displayed compatibility under in-vitro conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Al finalizar los ensayos, únicamente tres tratamientos mostraron una diferencia significativa (P<0.05) en todos los parámetros observados, en comparación al testigo de infección. Además, se determinó la interacción directa de los antagonistas con el patógeno y la reducción de una enfermedad en progreso, ya que, las plántulas fueron infectadas antes de la inoculación con los antagonistas (Rajeswari y Kapoor, 2018). Esto determina una efectiva colonización de los antagonistas y permite reducir la variabilidad del control de la enfermedad en el campo (Yendyo et al, 2017).…”
Section: Resultados Y Discusiónunclassified
“…The efficient role of 6PAP in the inhibition of biosynthesis of FA and its degradation has been described in Pseudomonas fluorescens [24]. Earlier studies have proved that the combined application of Trichoderma with Pseudomonas strains has improved activity than individual strains in biological control of diseases [25,26].…”
Section: Introductionmentioning
confidence: 99%